2014
DOI: 10.1021/ac403968d
|View full text |Cite
|
Sign up to set email alerts
|

Mixing in Colliding, Ultrasonically Levitated Drops

Abstract: Lab-in-a-drop, using ultrasonic levitation, has been actively investigated for the last two decades. Benefits include lack of contact between solutions and an apparatus and a lack of sample cross-contamination. Understanding and controlling mixing in the levitated drop is necessary for using an acoustically levitated drop as a microreactor, particularly for studying kinetics. A pulsed electrostatic delivery system enables addition and mixing of a desired-volume droplet with the levitated drop. Measurement of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…In the state-of-the-art levitation systems, 11,14,22,23,28 samples are manually inserted and removed with a syringe, requiring a skilled person to avoid sample losses and preventing the automation of the processes. Therefore, executing different fluidic operations such as injection, 19,29,30 transportation, 14,23,24 merging 14,26,28 and ejection 31 in a single levitation device would open up multiple possibilities, enabling the automatic processing of droplets in mid-air.…”
Section: Introductionmentioning
confidence: 99%
“…In the state-of-the-art levitation systems, 11,14,22,23,28 samples are manually inserted and removed with a syringe, requiring a skilled person to avoid sample losses and preventing the automation of the processes. Therefore, executing different fluidic operations such as injection, 19,29,30 transportation, 14,23,24 merging 14,26,28 and ejection 31 in a single levitation device would open up multiple possibilities, enabling the automatic processing of droplets in mid-air.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that the Z avg values for LEMS measurements were approximately the same suggests that the solution phase processes within the droplet are not important for laser vaporized protein. A droplet mixing experiment performed by colliding a 370 nL droplet of a basic solution containing phenolphthalein into an acoustically levitated 4 μL droplet of an acid showed that the basic solution remained on the surface for more than 2 s [51]. This time scale is larger than the~100 ms time scale that the protein spends with the ES droplet during the transit to the capillary inlet in LEMS measurements.…”
Section: Analysis Of Acid Sensitive Proteins (Cytochrome C and Myoglomentioning
confidence: 97%
“…During levitation, the gravitational force acting on the levitated droplet is balanced by the acoustic radiation force exerted on the droplet surface . Attractive features of the ultrasonic levitation include the compatibility with small droplet volumes (typically 5−10 μL, which is comparable to typical liquid marble volumes) and the ability to introduce contact‐less mixing and to change the droplet shape by changing the ultrasonic pressure. Ultrasonic levitation enables a container‐free environment that can resist surface confinement and contamination of the droplets and is highly desirable for sample manipulation, material fabrication and chemical analysis.…”
Section: Stimuli‐responsive Liquid Marblesmentioning
confidence: 99%